PENINGKATAN KUALITAS PELAYANAN IMB DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KOTA BOGOR DIWILAYAH KECAMATAN BOGOR TIMUR - Lulu Kristina; Rita Rahmawati; Euis Salbiah (LPPM Universitas Djuanda Bogor, 2018)
Increasing public demand is a logical consequence of the increasingly complex needs of the community on various matters, especially on service. On the other hand in line with one of the paradigms of government administration, namely Public Service (public service) government has an obligation to improve the quality of service that aims to the satisfaction of the community (driven customer).The purpose of this research is to analyze the implementation of the service of IMB (Building Permit), especially apparatus or human resources in charge of granting permission in East Bogor Subdistrict and To know the implementation of Building Construction Permit (IMB) in increasing the Original Revenue in Bogor Sub- East. The theory used in this research is by using service quality theory from Sinambela (2010) that is transparent, accountability, conditional, participative, equality of rights, balance of rights and obligation.The method used is descriptive analysis using Qualitative approach. While the data analysis technique used is by using the calculation of Weight Mean Score (WMS) and correlation coefficient rank spearman.Teknik data collection used is the study of literature and field studies. The unit of analysis of this study amounted to 30 Informants. While the sampling technique used is Accidental Sampling technique.The results of the Implementation of the Granting of Building Permit is done by referring to the Decision of the Governor of West Java Province No. 76 of 2000 on the procedure of obtaining IMB, IPB and KMB in the province of West Java and West Java Provincial Regulation No. 7 of 2010 About Building Buildings. Keywords: Quality of Kecamatan service, Building Permit (IMB), and Increased local revenue